2021
DOI: 10.1021/acsnano.1c05458
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Derived Ultrafine Sb@Porous Carbon Octahedron via In Situ Substitution for High-Performance Sodium-Ion Batteries

Abstract: Alloying-type anode materials are regarded as promising alternatives beyond intercalation-type carbonaceous materials for sodium storage owing to the high specific capacities. The rapid capacity decay arising from the huge volume change during Na+-ion insertion/extraction, however, impedes the practical application. Herein, we report an ultrafine antimony embedded in a porous carbon nanocomposite (Sb@PC) synthesized via facile in situ substitution of the Cu nanoparticles in a metal–organic framework (MOF)-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 66 publications
2
53
0
Order By: Relevance
“…Similar work involving of electrospun Sb/C as an SIBs anode was accomplished by Cao et al almost at the same time [46]. Afterwards, a variety of 1D Sb/C composite anodes have been established including Sb/CNT composite [38], peapod-like Sb@C [47], Sb@C coaxial nanotubes (Figure 2f) [48], N-doped carbon nanonecklaces with encapsulated Sb [49] and 1D yolk-shell Sb@Ti-O-P nanostructures [50]. Impressively, the full battery of Sb@Ti-O-P//Na 3 V 2 (PO 4 ) 3 -C presents a high output voltage (~2.7 V) and a capacity of 392 mAh g −1 after 150 cycles at 1 A g −1 .…”
Section: Sb/carbenecous Compositementioning
confidence: 76%
See 2 more Smart Citations
“…Similar work involving of electrospun Sb/C as an SIBs anode was accomplished by Cao et al almost at the same time [46]. Afterwards, a variety of 1D Sb/C composite anodes have been established including Sb/CNT composite [38], peapod-like Sb@C [47], Sb@C coaxial nanotubes (Figure 2f) [48], N-doped carbon nanonecklaces with encapsulated Sb [49] and 1D yolk-shell Sb@Ti-O-P nanostructures [50]. Impressively, the full battery of Sb@Ti-O-P//Na 3 V 2 (PO 4 ) 3 -C presents a high output voltage (~2.7 V) and a capacity of 392 mAh g −1 after 150 cycles at 1 A g −1 .…”
Section: Sb/carbenecous Compositementioning
confidence: 76%
“…In this way, the accurate structural information on the core-particle size, the void space and the complex structure can be systemically established (Figure 3b-e). Recently, metal-organic-framework (MOF) derived carbon has shown great capability to realize precise carbon-confined nanostructures with diverse compositions and delicate morphologies [38,39]. For example, Li et al reported an ultrafine Sb embedded in a porous carbon nanocomposite (Sb@PC) synthesized via a facile in situ substitution of the Cu nanoparticles in an MOF-derived octahedron carbon framework for sodium storage (Figure 3f).…”
Section: Sb/carbenecous Compositementioning
confidence: 99%
See 1 more Smart Citation
“…44 Huang et al fabricated an ultrafine Sb@PC octahedron through an in situ substitution using Cu(btc) 3 MOF as the templates. 2 When evaluated as the electrode for SIBs, the composite delivers a high reversible capacity of 634.6 mA h g −1 under a current density of 100 mA g −1 and prominent rate capability (298.2 mA h g −1 at 2.0 A g −1 ). Li et al reported CoSe 2 /N-doped carbon box from the sacrificial ZIF-67 templates, which shows excellent cycling performance (390.2 mA h g −1 at a current density of 5 A g −1 for 4000 cycles).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the limited lithium resources, uneven global distribution, and high manufacturing cost, lithium-ion batteries (LIBs) cannot meet the increasing demand for large-grid and renewable energy markets. [1][2][3][4] This compels scientists to explore alternative metal-ion batteries. In the past decade, sodium-ion batteries (SIBs) have been deemed as highly potential substitutes by virtue of their inexpensiveness and rich Na resources.…”
Section: Introductionmentioning
confidence: 99%